Community ecological succession of endophytic fungi associates with medicinal compound accumulation in Sophora alopecuroides - Mingxiu Ju; Qingchen Zhang; Ruotong Wang; Siyuan Yan; Qiangqiang Zhang; Peng Li; Fengxia Hao; Peiwen Gu (Microbiology Spectrum, 2024)
ABSTRACTEndophytic fungi of medicinal plants are symbiotic with the host and play an important role in determining metabolites. To understand the relationship between the accumulation of Sophora alopecuroides’ medicinal bioactive compounds and the ecological succession of endophytic fungi, here we collected samples from S. alopecuroides at four developmental stages (adult, flowering, podding, and mature) and different organs (roots, stems, leaves, and seeds) at the mature stage. We then used high-performance liquid chromatography-mass spectrometry and high-throughput sequencing on the internal transcribed spacer region to identify the medicinal compounds and endophytic fungal communities in each sample. The endophytic fungal community characteristics and accumulation of medicinally bioactive compounds of S. alopecuroides varied with the host’s developmental stages and organs, with the highest total alkaloids content of 111.9 mg/g at the mature stage. Membership analysis and network connection analysis showed a total of 15 core endophytic fungi in different developmental stages and 16 core endophytic fungi in different organs at the mature stage. The unclassified Ascomycota, Aspergillus, and Alternaria were significantly and positively correlated with the medicinal compounds of S. alopecuroides at the mature stage (r > 0.6 or r < −0.6; P < 0.05). In this study, we identified key endophytic fungal resources that affect the content of medicinally bioactive compounds in S. alopecuroides. This discovery could lay the foundation for enhancing the yield of medicinally bioactive compounds in S. alopecuroides and the development and application of functional endophytic fungi.IMPORTANCESophora alopecuroides is a traditional Chinese herbal medicine. The major medicinal chemicals are considered to be quinolizidine alkaloids. Quinolizidine alkaloids have been widely used for the treatment of tumors, dysentery, and enteritis. Previous studies have found that endophytic fungi in S. alopecuroides can promote the accumulation of host quinolizidine alkaloids. However, the relationship between the accumulation of S. alopecuroides’ medicinal bioactive compounds and the ecological succession of endophytic fungi remains unclear. In this study, we screened the key endophytic fungal resources affecting the content of medicinally bioactive compounds and laid the foundation for subsequent research on the mechanism by which endophytic fungi promote the accumulation of medicinally bioactive compounds in S. alopecuroides.